El ogro Zeralda - Ungerer, Tomi, 1931- (Boulder, Colo. : TomiCo, 1999)
The giant appetite of the ogre could only be satisfied by the flesh of children until young Zeralda tamed his taste buds with her culinary art.
Originally published 1967.
4.2
K-3
K-3.
Keywords: Fairy tales; Fairy tales